2010
DOI: 10.1124/dmd.109.031377
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypothermia Alters Midazolam Pharmacokinetics in Normal Healthy Volunteers

Abstract: ABSTRACT:The clinical use of therapeutic hypothermia has been rapidly expanding due to evidence of neuroprotection. However, the effect of hypothermia on specific pathways of drug elimination in humans is relatively unknown. To gain insight into the potential effects of hypothermia on drug metabolism and disposition, we evaluated the pharmacokinetics of midazolam as a probe for CYP3A4/5 activity during mild hypothermia in human volunteers. A second objective of this work was to determine whether benzodiazepine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 36 publications
(34 reference statements)
3
43
1
1
Order By: Relevance
“…A total of 15 CA patients who underwent hypothermic treatment to 33-34°C were enrolled in this case-control study and matched to critically ill patients in the ICU, who did not receive hypothermia (n = 8). In contrast to Hostler et al (2010), the investigators found no difference in the volume of distribution (V D ), Cl, or elimination half-life (t 1/2 ) of midazolam between the hypothermic patients and the normothermic controls. This study involved a relatively small number of subjects with significant interindividual variability in the midazolam time-concentration profiles in both groups.…”
Section: Sedatives/anestheticsmentioning
confidence: 71%
See 1 more Smart Citation
“…A total of 15 CA patients who underwent hypothermic treatment to 33-34°C were enrolled in this case-control study and matched to critically ill patients in the ICU, who did not receive hypothermia (n = 8). In contrast to Hostler et al (2010), the investigators found no difference in the volume of distribution (V D ), Cl, or elimination half-life (t 1/2 ) of midazolam between the hypothermic patients and the normothermic controls. This study involved a relatively small number of subjects with significant interindividual variability in the midazolam time-concentration profiles in both groups.…”
Section: Sedatives/anestheticsmentioning
confidence: 71%
“…Midazolam is in the benzodiazepine class of drugs and is commonly administered as a sedative in the ICU. Hostler et al (2010) randomized six healthy volunteers to (Hostler et al, 2010). Bjelland et al (2013) investigated the effects of hypothermia on the disposition of midazolam along with several other sedatives and anesthetics (fentanyl, morphine, and propofol) in patients suffering from CA.…”
Section: Sedatives/anestheticsmentioning
confidence: 99%
“…Elimination of fentanyl was essentially stopped in children cooled to 18-25°C (Koren et al, 1987). The effect of hypothermia on clearance of midazolam in humans has been reported to vary from naught to more than 100-fold, and an 11.1% reduction in clearance per degree of reduced core temperature was estimated (Fukuoka et al, 2004;Hostler et al, 2010). The metabolism of propofol in humans depends on liver flow and involves several enzymes such as UGT1A8/9, CYP2C9, and CYP2B6.…”
Section: Introductionmentioning
confidence: 99%
“…Se sugiere una temperatura de 32 a 35 °C, por 24 a 48 h (32). Pero puede haber reducción de la depuración de algunos anestésicos como del midazolam que disminuye 11,1% por cada grado celsius de reducción de la temperatura corporal por debajo de 36,5°C (33).…”
Section: Hipotermiaunclassified